Differences in Clinical Characteristics Between Delta Variant and Wild-Type SARS-CoV-2 Infected Patients - Hu, Zhenkui; Huang, Xing; Zhang, Jianguo; Fu, Shixiang; Ding, Daoyin; Tao, Zhimin (Frontiers in Medicine, 2022)
Background: As delta variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) prevailed in current coronavirus disease 2019 (COVID-19) pandemic, its clinical characteristics with difference from those of wild-type strains have been little studied. Methods: We reported one cohort of 361 wild-type COVID-19 patients admitted at Wuhan, China in 2020 and the other cohort of 336 delta variant COVID-19 patients admitted at Yangzhou, China in 2021, with comparisons of their demographic information, medical history, clinical manifestation, and hematological data. Furthermore, within delta variant cohort, patients with none, partial and full vaccination were also compared to assess vaccine effectiveness. Findings: For a total of 677 COVID-19 patients included in this study, their median age was 53.0 (IQR: 38.0-66.0) and 46.8% was male. No difference was found in age, gender, and per centage of patients with the leading comorbidity between wild-type and delta variant cohorts, but delta variant cohort showed a lessened time interval between disease onset to hospitalization, a reduced portion of patients with smoking history and a lowered frequency of clinical symptoms. For hematological parameters, most values demonstrated significant differences between wild-type and delta variant cohorts, while full vaccination rather than partial vaccination alleviated the disease condition. This reflected the viremic effect of delta variant when vaccination succeeds in or fails to protect. Interpretation: Delta variant of SARS-CoV-2 may cause severe disease profiles, but timely diagnosis and full vaccination could protect COVID-19 patients from worsened disease progression.